2019
DOI: 10.1007/s13197-019-03636-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of chlorine dioxide microcapsule sustained-release antibacterial films for preservation of mangos

Abstract: In this study, fresh mangos were packed using a custom-made antimicrobial film coated with sustained-release chlorine dioxide microcapsules. We then compared physical and chemical indexes, such as weight loss rate, firmness, chromatic aberrations, soluble solids, vitamin C, titratable acid, and other nutritional indicators, to examine changes in the mango and film during storage. Our findings revealed that control mango showed loss of edible value and commercial value after 21 days of storage, and the chlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…On the 14th day, b* value of uncoated papayas reached 58.1. However, the b* value of coated papayas was lower and increased slower, as previously reported by others working with other fruits such as mango [39]. Papayas coated with two, four or six layers showed b* values of 44.1, 37.6 and 42.6, respectively, all of which were lower than that of the single-layer coating (P < 0.05).…”
Section: Colorsupporting
confidence: 79%
“…On the 14th day, b* value of uncoated papayas reached 58.1. However, the b* value of coated papayas was lower and increased slower, as previously reported by others working with other fruits such as mango [39]. Papayas coated with two, four or six layers showed b* values of 44.1, 37.6 and 42.6, respectively, all of which were lower than that of the single-layer coating (P < 0.05).…”
Section: Colorsupporting
confidence: 79%
“…Antimicrobial film-forming materials are developed by incorporating the antimicrobial agents into a polymer matrix which allows their release onto the food surface to interact with the microflora. Zhang et al [ 72 ] investigated the effect of a custom-made antimicrobial film by applying a coating containing sustained-release chlorine dioxide microcapsules on fresh mangos. According to a study reported by Ghaouth et al [ 73 ], chitosan-coated tomatoes were adequately protected from Penicillium spp., Aspergillus spp., Rhizopus stolonifer , and Botrytis cinerea .…”
Section: Protection Of Fruits and Vegetables By Appropriate Packaging Methodsmentioning
confidence: 99%
“…Using the direct weighing method described by Zhang et al [31], the samples were weighed using an electronic balance (PL601-L; METTLER TOLEDO Instrument Co., Ltd., Zurich, Switzerland) before being coated. Before each sampling, the samples were weighed.…”
Section: Methodsmentioning
confidence: 99%